Effect of Compensation, Career Development and Work Environment on Employee Retention (Study on Employees of PT Telkom Witel Tangerang BSD) - Agtovia Frimayasa (Kusuma Negara Business School, 2021)
Human resources (HR) are an important factor in the development process of a company. Without good human resources, a company will not develop properly, because even though a company has a good system and sophisticated technology, if it is not supported by competent human resources, the goals of achieving the company's targets will not be achieved effectively and efficiently. One of the focuses of HR management is employee retention. Employee retention is the process of how to encourage employees to stay with the organization for a maximum time or until the completion of a project, employee retention is the company's ability to retain employees who have the potential to remain loyal to the company. The purpose of this research is to study and analyze the effect of compensation, career development and work environment either partially or simultaneously on employee retention of PT Telkom Witel Tangerang BSD. The research data were collected by distributing questionnaires, the collected data were processed using the Structural Equation Model method with Smart PLS software tools. The results of this study indicate that compensation has a positive and significant effect on employee retention. Career development has no effect on employee retention. The work environment has no effect on employee retention.